ATENÇÃO A SAÚDE DA GESTANTE SOB A PERSPECTIVA MULTIDISCIPLINAR DA RESIDÊNCIA EM SAÚDE - Scherer, Cristiane; Schimitz, Ernani; Ubessi, Liamara D.; Gandez, Sabrina D. (Salão do Conhecimento, 2013)
Resumo